ACCELERATION OF ECHINACEA PURPUREA (L.) MOENCH SHOOT GROWTH BY BENZYL ADENINE AND INDOLE BUTYRIC ACID ADDITION - Wijaya, Nur Rahmawati; Sudrajad, Heru (Universitas Muhammadiyah Yogyakarta, 2019)
Echinacea (Echinacea purpurea (L.) Moench) is a medicinal plant known to boost the immune system. Propagation is necessary to increase production. One of the methods of propagation in tissue culture. This research was conducted to understand the most suitable concentration of plant growth regulators. The treatment was given a combination of Benzyl Adenine (BA) and Indole Butyric Acid (IBA) with BA concentration of 1 ppm, 2 ppm, 3 ppm and 4 ppm while the IBA concentration used was 1 ppm and 2 ppm. The next step was subculture by using the combination among IBA 0 ppm, 0.5 ppm, 0.75 ppm and BAP 0 ppm, 0.5 ppm, 0.75 ppm of BAP. The result showed that the most shoots produced by the combination treatment of BA 2 ppm and IBA 1 ppm while the highest shoot and leaf number is best produced in treatment BA 1 ppm and IBA 2 ppm. The largest number of shoots was shown by treatment BA 2 ppm and IBA 1 ppm. This study can be concluded that BA 1 ppm and IBA 2 ppm, and BA 2 ppm and IBA 1 ppm gave the best treatment for shoot growth and control for root induction.